Analysis of Transistor Open Fault Diagnosis for Shunt Active Power Filters - Benyettou Loutfi; T. Benslimane (Institute of Advanced Engineering and Science, 2017)
In this paper a transistor open-circuit fault diagnosis problem in two-level voltage inverter controlled shunt active power filter drives was discussed. Taking into consideration requirements of the contemporary monitoring drive systems original transistor fault diagnostic technique were proposed. Presented results were obtained by designed in PSIM software simulation model.